Activated protein C attenuates ischemia-reperfusion-induced acute lung injury. (1st June 2015) - Lan, Chou-Chin; Peng, Chung-Kan; Huang, Shiu-Feng; Huang, Kun-Lun; Wu, Chin-Pyng
ABSTRACT Ischemia-reperfusion (IR)-induced acute lung injury (ALI) is implicated in several clinical conditions, such as lung transplantation, acute pulmonary embolism after thrombolytic therapy, re-expansion of collapsed lung from pneumothorax, or pleural effusion, cardiopulmonary bypass, etc. Because mortality remains high despite advanced medical care, prevention and treatment are important clinical issues. Activated protein C (APC) manifests multiple activities with antithrombotic, profibrinolytic, and anti-inflammatory effects. We therefore conducted this study to determine the beneficial effects of APC in IR-induced ALI. IR-induced ALI was conducted in a rat model of isolated-perfused lung in situ. The animals were divided into the control group, IR group, and IR+APC group. There were six adult male Sprague–Dawley rats in each group. The IR caused significant pulmonary microvascular hyperpermeability, pulmonary edema and dysfuction, increased cytokines (tumor necrosis factor (TNF)-α, IL-17, CXCL-1), and neutrophils infiltration in lung tissues. Administration of APC significantly attenuated IR-induced ALI with improving microvascular permeability, pulmonary edema, pulmonary dysfunction, and suppression inflammatory response. The current study demonstrates the beneficial effects of APC in IR-induced ALI. This protective effect is possibly associated with the inhibition of TNF-α, IL-17A, CXCL1, and neutrophils infiltration in lung tissues. However, the current results were obtained in an animal model and it is still necessary to confirm these findings in human subjects. If we can demonstrate the benefits of APC to protect IR lung injury, we can postulate that APC is a potential therapeutic drug for lung preservation.